The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.5999/aps.2021.00808
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric change of the latissimus dorsi muscle after postoperative chemotherapy and radiotherapy in immediate breast reconstruction with an extended latissimus dorsi musculocutaneous flap: final results from serial studies

Abstract: Background Breast reconstruction using an extended latissimus dorsi (eLD) flap can supplement more volume than reconstruction using various local flaps after partial mastectomy, and it is a valuable surgical method since the reconstruction area is not limited. However, when performing reconstruction, the surgeon should consider latissimus dorsi (LD) volume reduction due to postoperative chemotherapy (POCTx) and postoperative radiotherapy (PORTx). To evaluate the effect of POCTx and PORTx on LD volume reduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Previous studies have reported that muscle denervation causes atrophy 6,16 . However, to the best of our knowledge, no study has reported the measurement of the degree of atrophy in reinnervated free muscle transfer.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Previous studies have reported that muscle denervation causes atrophy 6,16 . However, to the best of our knowledge, no study has reported the measurement of the degree of atrophy in reinnervated free muscle transfer.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies have reported that muscle denervation causes atrophy. 6,16 However, to the best of our knowledge, no study has reported the measurement of the degree of atrophy in reinnervated free muscle transfer. To accurately compare the volume change of reinnervated and denervated muscles, it is necessary to compare the conventional ALT MC flap without neurorrhaphy and the dynamic ALT flap.…”
Section: Discussionmentioning
confidence: 99%
“…There are various opinions about the cause of the decrease in the volume of the flap over time. In case of muscle flap, atrophy is known to occur because of denervation, 2 but in case of fasciocutaneous flap, transitional ischemic effect has been suggested as the cause 1,9 . In addition, it is hypothesized that the relief of edema and inflammation after surgery also affects volume reduction.…”
Section: Discussionmentioning
confidence: 99%
“…However, the change in flap volume is an unavoidable phenomenon over time. 1,2 As most of the musculature of the tongue is resected in total tongue reconstruction, there are some studies focusing on the reconstruction of volume and function. 3,4 However, in partial tongue reconstruction, some muscles and functions remain; therefore, a small flap is mainly used, and interest in changes after surgery is relatively low.…”
mentioning
confidence: 99%
See 1 more Smart Citation